Associations between gait coordination, variability and motor cortex inhibition in young and older adults - Swanson, Clayton W., author; Fling, Brett W., advisor; Lodha, Neha, committee member; Burzynska, Agnieszka, committee member (Colorado State University. Libraries, 2018)
Interlimb coordination and mobility (postural sway and turning) diminish with age, posing a risk for gait-related injuries. Further, levels of inhibition within the motor cortex are significantly associated with coordination of the upper extremities in healthy aging, however, it is unknown if this same association exists for lower extremity control. To investigate the relationship between gait coordination and cortical inhibition we measured gait coordination via the phase coordination index and motor cortex inhibition via the cortical silent period in 14 young and 15 older adults. Gait coordination was reduced in older adults across a variety of walking conditions, as was cortical inhibition, solely in the non-dominant motor cortex. Furthermore, young adults were better able to maintain lower extremity coordination and variability with reduced cortical inhibition, whereas older adults with increased cortical inhibition demonstrated better walking performance. These findings suggest a fundamental shift in the relationship between motor cortex inhibition and lower extremity control with age, similar to previous work demonstrating an age-related difference in the association between motor cortex inhibition with bimanual control.